Residue 6.43 defines receptor function in class F GPCRs - Ainoleena Turku (Nature Portfolio, 2021)
The class Frizzled of G protein-coupled receptors (GPCRs) consist of ten Frizzled (FZD1-10) subtypes and Smoothened (SMO). Here the Schulte laboratory demonstrates that FZDs differ substantially from SMO in receptor activation-associated conformational changes, while SMO manifests a preference for a straight TM6, the TM6 of FZDs is kinked upon activation.